A companion to the preclinical common data elements and case report forms for in vivo rodent neuroimaging: A report of the TASK3‐WG3 Neuroimaging Working Group of the ILAE/AES Joint Translational Task Force - Erwin A. vanVliet; Riikka Immonen; Ofer Prager; Alon Friedman; Jens P. Bankstahl; David K. Wright; Terence J. O'Brien; Heidrun Potschka; Olli Gröhn; Neil G. Harris (Epilepsia Open)
Abstract The International League Against Epilepsy/American Epilepsy Society (ILAE/AES) Joint Translational Task Force established the TASK3 working groups to create common data elements (CDEs) for various aspects of preclinical epilepsy research studies, which could help improve the standardization of experimental designs. In this article, we discuss CDEs for neuroimaging data that are collected in rodent models of epilepsy, with a focus on adult rats and mice. We provide detailed CDE tables and case report forms (CRFs), and with this companion manuscript, we discuss the methodologies for several imaging modalities and the parameters that can be collected.